THE INFLUENCE OF TRACE AMOUNTS OF WATER ON THE VISCOSITY OF RHYOLITES - Stevenson R.J.; Bagdassarov N.S.; Dingwell D.B.; Romano C. (My University, 1998)
As a major volatile in volcanic systems, water has a significant influence on the rheological properties of silicic magmas. This is especially so at minor water contents relevant to the emplacement of silicic lavas. To investigate the influence of water on the viscosity of natural rhyolitic obsidians, a novel strategy has been adopted employing parallel-plate and micropenetration techniques. Viscosities have been determined on three types of material: (a) raw water-bearing obsidians; (b) remelted (1650 °C, 1 atm) degassed glasses of the obsidians; and (c) hydrothermally hydrated (1300 °C, 3 kbar) obsidians. Ten natural rhyolitic obsidians (peraluminous, calc-alkaline and peralkaline) were employed: seven originated from lava flows and contained <0.2 wt.% H2O, two samples were F-rich from pyroclastic successions, and one was an obsidian cobble with 1.5 wt.% water also associated with pyroclastic units. Melt compositions and water contents were stable during viscometry. The measured decreases in activation energies of viscous flow and viscosity with small amounts of water are much greater than the Shaw calculation scheme predicts. In addition, a marked non-linear decrease in η exists with increasing water content. In contrast to the case for peralkaline rhyolites, 0.1-0.2 wt.% water decreases activation energies significantly (up to 30%) for calc-alkaline compositions. These results have important implications for the ease of near-surface degassing of silicic magmas during emplacement and permit the testing of calculational models for viscosity, largely based on synthetic systems.
Keywords: RHYOLITE; CALC-ALKALINE; PERALKALINE; VISCOSITY; WATER; ACTIVATION ENERGY